2020
DOI: 10.1108/ijssp-07-2020-0297
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in a collectivist culture: social isolation and maintenance of social relations

Abstract: PurposeThe purpose of this paper is to investigate the way people in a collectivist culture, particularly Egyptians, define social isolation and to understand the effect of social isolation on maintaining traditional networks of social relations.Design/methodology/approachTo do this, online ethnographic semi-structured interviews were carried out with a purposeful sample of non-infected Egyptians who have access to social media networks.FindingsAlthough collectivism may be perceived as a risk factor in develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Hence, it appears that in-group collectivism or kinship bonds have been especially helpful in coping with natural calamities (e.g., Fincher & Thornhill, 2012). Furthermore, a qualitative study of Egyptians during Covid-19 outbreak explicitly mentions that in-group collectivism helps (Hussein, 2020). In contrast, this study finds that in the presence of institutional collectivism, in-group collectivism seems neither effective in mitigating morbidity, nor does it seem to help curb mortality.…”
Section: Discussionmentioning
confidence: 67%
“…Hence, it appears that in-group collectivism or kinship bonds have been especially helpful in coping with natural calamities (e.g., Fincher & Thornhill, 2012). Furthermore, a qualitative study of Egyptians during Covid-19 outbreak explicitly mentions that in-group collectivism helps (Hussein, 2020). In contrast, this study finds that in the presence of institutional collectivism, in-group collectivism seems neither effective in mitigating morbidity, nor does it seem to help curb mortality.…”
Section: Discussionmentioning
confidence: 67%
“…At first glance, this finding may not seem very revealing. The social sciences have long documented the role of community ties in providing various kinds of support (Cattell, 2001;Wellman & Wortley, 1990), and recent studies conducted worldwide have shown that these relationships were indeed activated in response to COVID-19 (Hussein, 2022;Igwe et al, 2020). However, in the French context, exposing this dimension in a report to the government is close to a revelation.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Even at the level of individual experience of the pandemic's effects, individualism has been linked to higher experienced stress and isolation [19]. Some emerging research on the experience of social isolation amidst an ongoing pandemic suggests that collectivist societies are better equipped to deal with social isolation beget by pandemic conditions, with worry, fear, and anxiety being kept in check through networks of social connections [3]. Recent research has in fact shown that an individualist mindset led to a reduced intention to vaccinate compared with collectivism [35].…”
Section: Covid-19 and Cultural Differences Between Individualism And ...mentioning
confidence: 99%
“…Governments and people across the world have been left scrambling to contain the spread of the virus and to adopt effective risk mitigation strategies, even after pharmaceutical interventions such as vaccines have come on the horizon [2]. The scale of damage that the SARS-CoV-2 virus has unleashed in terms of the lives lost, harmful mental and physical health consequences [3], and constraints on public health systems [4] has been unprecedented. As of May 2022, more than 520 million cases of COVID-19 and 6.2 million fatalities have been reported worldwide, with the United States, India, Brazil, France, Germany, the United Kingdom, and Russia having reported the largest number of cases [5].…”
Section: Introductionmentioning
confidence: 99%